Selenite Reduction by Anaerobic Microbial Aggregates: Microbial Community Structure, and Proteins Associated to the Produced Selenium Spheres - Gonzalez-Gil, Graciela; Lens, Piet N. L.; Saikaly, Pascal E. (Frontiers in Microbiology, 2016)
Certain types of anaerobic granular sludge, which consists of microbial aggregates, can reduce selenium oxyanions. To envisage strategies for removing those oxyanions from wastewater and recovering the produced elemental selenium (Se0), insights into the microbial community structure and synthesis of Se0 within these microbial aggregates are required. High-throughput sequencing showed that Veillonellaceae (c.a. 20 %) and Pseudomonadaceae (c.a.10 %) were the most abundant microbial phylotypes in selenite reducing microbial aggregates. The majority of the Pseudomonadaceae sequences were affiliated to the genus Pseudomonas. A distinct outer layer (~200 m) of selenium deposits indicated that bioreduction occurred in the outer zone of the microbial aggregates. In that outer layer, SEM analysis showed abundant intracellular and extracellular Se0 (nano) spheres, with some cells having high numbers of intracellular Se0 spheres. Electron tomography showed that microbial cells can harbor a single large intracellular sphere that stretches the cell body. The Se0 spheres produced by the microorganisms were capped with organic material. X-ray photoelectron spectroscopy (XPS) analysis of extracted Se0 spheres, combined with a mathematical approach to analyzing XPS spectra from biological origin, indicated that proteins and lipids were components of the capping material associated to the Se0 spheres. The most abundant proteins associated to the spheres were identified by proteomic analysis. Most of the proteins or peptide sequences capping the Se0 spheres were identified as periplasmic outer membrane porins and as the cytoplasmic elongation factor Tu protein, suggesting an intracellular formation of the Se0 spheres. In view of these and previous findings, a schematic model for the synthesis of Se0 spheres by the microorganisms inhabiting the granular sludge is proposed.